Implementation of the Integrated Village Economic Transformation Program (TEKAD) in Efforts to Develop Village Potential and Community Empowerment - Jehuma, Blasius Febri; Pellokila, Marthen Robhinson; Tiwu, Maria Indriyani Hawe (Jurnal Ekonomi Balance, 2024)
This study explores the implementation of the TEKAD Integrated Village Economic Transformation program to enhance village potential and community empowerment in Bea Kakor Village. Employing the Analytical Hierarchy Process (AHP) and Descriptive Analysis, the research identifies key factors crucial to the TEKAD program's success. The prioritized aspects, in descending order, are human resources, infrastructure, natural resources, and institutions. In the contemporary context, many villages struggle to unlock their potential due to historical centralistic development models, resulting in untapped resources and limited creativity. In response, the TEKAD program, initiated under Presidential Regulation No. 3 of 2016, aims to empower rural communities and boost economic development through active community involvement. The study focuses on Bea Kakor Village within the TEKAD program in East Nusa Tenggara, highlighting the pivotal role of human resources, infrastructure, and natural resources. The research utilizes the AHP method to prioritize these factors, emphasizing the significance of human resources in driving economic growth. The findings provide valuable insights for policymakers and community leaders to enhance the effectiveness of TEKAD and similar programs in fostering sustainable development and inclusive economic growth.